TRANSFORMASI DIGITAL LAYANAN PENDIDIKAN: INTEGRASI ADMINISTRASI PUBLIK DAN MANAJEMEN PENDIDIKAN DI ERA SMART GOVERNANCE - Rahim Kausar; Muhammad Ihsan (Jurnal Humaniora & Sosial Sains, 2025)
Digital transformation is a determining factor in driving the modernization of education services in the era of smart governance, where information technology serves as a strategic instrument to increase effectiveness, transparency, and accountability in the delivery of public services. A governance approach based on digital intelligence demands integration between public administration principles and educational management practices to build an adaptive, data-driven education governance system that is able to respond to the dynamics of community needs. This article examines the role of digitalization not only as a technical tool but also as a transformational force that reshapes the structure, processes, and direction of education policy. The analysis findings indicate that the effectiveness of digital transformation in the education sector is determined by four main factors: policy alignment between agencies and across levels of government, the availability and equitable distribution of digital infrastructure, increased competency and digital literacy of human resources, including civil servants and educators, and an organizational culture that supports innovation, collaboration, and evidence-based decision-making. The connection between public administration and educational management is a crucial foundation for realizing inclusive, effective, and sustainable education governance. This article provides a theoretical contribution to developing an understanding of the digitalization of education services and offers policy implications for the government in strengthening smart governance practices.